Compound heterozygous mutations Glu502Lys and Met527Thr of the FXII gene in a patient with factor XII deficiency. Issue 1 (1st January 2019) - Zhang, Haiyue; Liu, Siqi; Lin, Chanchan; Luo, Shasha; Yang, Lihong; Jin, Yanhui; Zhu, Liqing; Wang, Mingshan
ABSTRACT: Objective : To study the gene mutation of human coagulation factor XII (FXII) in a Chinese family with FXII deficiency and it will help us to understand the pathogenesis of this type of disease. Clinical presentation : The proband was a 50-year-old male who had a fracture of the right humerus. The routine presurgical coagulation test showed a significant prolonged activated partial thromboplastin time (APTT) at 59.1s (reference range, 29.0–43.0s). Techniques : FXII activity (FXII:C) and FXII antigen (FXII:Ag) were detected by the one-stage clotting method and ELISA, respectively. To identify mutations, the FXII whole exon and flanking sequences were carried out. Suspected mutations were confirmed by reverse sequencing. The conservatism and possible impact of the amino acid substitution were analyzed by ClustalX-2.1-win and four online bioinformatics tools. Results : Phenotypic analysis revealed the FXII:C and FXII:Ag of the proband were 4% and 5%, respectively (normal range, 72–113%). Gene sequencing detected compound heterozygous mutations c.1561G > A (Glu502Lys) and c.1637T > C (Met527Thr) in exon 13. Bioinformatics and model analysis indicated that mutations probably had disrupted the function and structure of the FXII protein. Conclusion : We detected two missense mutations Glu502Lys and Met527Thr in the catalytic domain of the proband, of which Met527Thr was first reported in the world. Our findings suggest that the double mutations in the FXII gene were the causing reasons for the decreased FXII:C and FXII:Ag. These results not only enriched the F12 mutation database in this condition, but also helped to identify the genetic defects of FXII in China.